Risk factors for ventilator-associated pneumonia in patients with severe traumatic brain injury in a Serbian trauma centre. (September 2015) - Jovanovic, Bojan; Milan, Zoka; Markovic-Denic, Ljiljana; Djuric, Olivera; Radinovic, Kristina; Doklestic, Krstina; Velickovic, Jelena; Ivancevic, Nenad; Gregoric, Pavle; Pandurovic, Milena; Bajec, Djordje; Bumbasirevic, Vesna
Summary: Introduction: The aims of this study were (1) to assess the incidence of ventilator-associated pneumonia (VAP) in patients with traumatic brain injury (TBI), (2) to identify risk factors for developing VAP, and (3) to assess the prevalence of the pathogens responsible. Patients and methods: The following data were collected prospectively from patients admitted to a 24-bed intensive care unit (ICU) during 2013/14: the mechanism of injury, trauma distribution by system, the Acute Physiology and Chronic Health Evaluation (APACHE) II score, the Abbreviated Injury Scale (AIS) score, the Injury Severity Score (ISS), underlying diseases, Glasgow Coma Scale (GCS) score, use of vasopressors, need for intubation or cardiopulmonary resuscitation upon admission, and presence of pulmonary contusions. All patients were managed with a standardized protocol if VAP was suspected. The Sequential Organ Failure Assessment (SOFA) score and the Clinical Pulmonary Infection Score (CPIS) were measured on the day of VAP diagnosis. Results: Of the 144 patients with TBI who underwent mechanical ventilation for >48 h, 49.3% did not develop VAP, 24.3% developed early-onset VAP, and 26.4% developed late-onset VAP. Factors independently associated with early-onset VAP included thoracic injury (odds ratio (OR) 8.56, 95% confidence interval (CI) 2.05–35.70; p  = 0.003), ISS (OR 1.09, 95% CI 1.03–1.15; p  = 0.002), and coma upon admission (OR 13.40, 95% CI 3.12–57.66; p  < 0.001). Age (OR 1.04, 95% CI 1.02–1.07; p  = 0.002), ISS (OR 1.09, 95% CI 1.04–1.13; p  < 0.001), and coma upon admission (OR 3.84, 95% CI 1.44–10.28; p  = 0.007) were independently associated with late-onset VAP (Nagelkerke r 2  = 0.371, area under the curve (AUC) 0.815, 95% CI 0.733–0.897; p  < 0.001). The 28-day survival rate was 69% in the non-VAP group, 45.7% in the early-onset VAP group, and 31.6% in the late-onset VAP group. Acinetobacter spp was the most common pathogen in patients with early- and late-onset VAP. Conclusions: These results suggest that the extent of TBI and trauma of other organs influences the development of early VAP, while the extent of TBI and age influences the development of late VAP. Patients with early- and late-onset VAP harboured the same pathogens.